Earning a living, but at what price? Being a motorcycle taxi driver in a Sub-Saharan African city - (:unkn) unknown (My University, 2016)
Motorcycle taxis have become an essential part of the transport sector in an increasing number of Sub-Saharan African cities. An analysis of the way this activity operates in Lomé (Togo), based on field surveys, provides a better understanding of the reasons for the development of this transport mode. The majority of drivers earn enough from the activity to meet their day to day needs and to invest to increase human and economic capital. The arduous working conditions, the impacts on health and the risk of accidents and aggression explain however why 2 the activity is perceived as temporary and undertaken for want of anything better. There is a need to identify measures to professionalise the occupation and improve its image, and also find the best way to implement them. The occasionally stated goal of doing away with motorcycle taxis in order to modernize urban transport systems would have negative effects on their livelihoods.
Keywords: African Research